Critical Reading of Tunjuk Ajar Melayu Texts Regarding Humanist Literacy as Conservation Teaching Materials Language Learning in the Millennial Era - Asnawi Asnawi; Ida Zulaeha; Teguh Supriyanto; Hari Bakti Mardikantoro; Sri Wahyuni; Fauzul Etfita (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to describe the characteristics of teaching materials for critical reading of Tunjuk Ajar Melayu texts that link the humanist literacy desired by lecturers and students in Riau Province, Indonesia. This research is a qualitative approach with a descriptive method. The research data are in the form of questionnaires and interviews from research respondents. The respondents of this study involved lecturers and students in Riau Province. Data validation is done by triangulation of sources and methods. Furthermore, data analysis was carried out reflectively with the help of TagCrowd and AntCont. Based on the study that has been carried out, it is found that the characteristics of critical reading teaching materials desired by students and lecturers in Riau Province include, (1) teaching materials must be oriented towards humanist literacy activities, (2) use the Tunjuk Ajar Melayu text, (3) be oriented towards an attitude approach. and behavior (psychodidactic), (4) has material that is in accordance with the characteristics of Malay culture, (5) has language that is in line with the context of Malay language and culture, and (6) presentation uses Malay icons which are arranged in detail and systematically. The implications of the results of this study can be to construct and conserve critical reading learning and critical reading teaching materials for the Tunjuk Ajar Melayu text to create student understanding in understanding and integrating humanist values in everyday life. Humanist awareness is important to be formed in facing the challenges of language learning in the millennial era.